Somatic Embryogenesis of Carica Papaya Cv. Eksotika - Beverlien, Christine (2005)
This study was carried out with the main objective of establishing somatic embryo production in Carica papaya cv. Eksotika that can be used for further genetic improvement of the crop. The study included induction of somatic embryogenesis from immature zygotic embryos and anatomical study of the embryo development, establishment of plant regeneration from the somatic embryo, and establishment of cell suspension culture from embryogenic callus.